THE EFFECT OF INTERPERSONAL SKILLS INTEGRATION IN CLASSROOM ACTIVITIES - GOURA, Fatima (l’Université de Mostaganem, 2022)
A considerable literature has grown up around the theme of integrating interpersonal communication in the educational contexts and many studies have emphasised the positive impact of those skills on learning outcomes. Despite the vast research in this area, little is known on the possible pedagogical implications that can be conveyed through integrating interpersonal skills in teaching English as a foreign language. Hence, this work aims at investigating the effect of interpersonal skills integration in English language teaching settings and on learners’ communication. Therefore, this study seeks the potential strategies and techniques to develop third grade Algerian middle school learners’ interpersonal skills to be used both inside and outside the classroom. Hence, the type of methodology adopted in this study is the quasi-experimental research with a pre-test/ post-test design. The research aimed at measuring the learning outcomes of teaching four dimensions of interpersonal skills namely, clarity of expression, active listening, receptive feedback, and self-regulation. The sample included two sections: one experimental group and one control group. Learners of the first group (n=15) have received the teaching intervention while those of the second group (n=15) have attended regular classes for the same period of time. Besides, two research tools were selected which are the Self-Perceived Communicative Competence Scale and the Interpersonal Communicative Skills Inventory. The results elucidated that the integration of a multi-model teaching intervention of interpersonal skills made a significant improvement in learners’ self-perceived communication which is a major indicator of their willingness to communicate. Accordingly, some recommendations were suggested to make interpersonal communicative teaching a standard practice in the Algerian English Language teaching settings.
Keywords: active listening; clarity of expression; communication; interpersonal skills; receptive feedback; self-regulation